2012
DOI: 10.1002/chir.22086
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Absolute Configurations of 3‐Alkylphthalides using TDDFT Calculations of Chiroptical Properties

Abstract: Absolute configurations (ACs) of 3-alkylphthalides including natural products (-)-3-n-butylphthalide ((-)-1) and fuscinarin have been studied using chiroptical properties and quantum chemical calculation. Electronic circular dichroism and optical rotatory dispersion spectra of (S)-1 predicted adopting time-dependent density functional theory and hybrid functionals coincide very well with the experimental and literature data of (-)-1, leading unambiguously to AC assignment as S for levorotatory isomer. The rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…However, it might be interesting and useful to establish directly their stereochemistry without reference samples and spectra. Presently, ECD spectra together with quantum chemical calculations using time-dependent density functional theory (TDDFT) have provided a feasible and reliable way to facilitate the AC assignments of chiral drugs and natural products [ 15 , 18 , 40 , 41 , 42 , 43 , 44 ]. Hence, TDDFT calculations will be adopted to simulate ECD spectra of sulfoxides in this study.…”
Section: Introductionmentioning
confidence: 99%
“…However, it might be interesting and useful to establish directly their stereochemistry without reference samples and spectra. Presently, ECD spectra together with quantum chemical calculations using time-dependent density functional theory (TDDFT) have provided a feasible and reliable way to facilitate the AC assignments of chiral drugs and natural products [ 15 , 18 , 40 , 41 , 42 , 43 , 44 ]. Hence, TDDFT calculations will be adopted to simulate ECD spectra of sulfoxides in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Reaction (±) 8 with (S)-O-methyl mandelic acid provided a pair of diastereomeric esters 16 ( 17 (R f = 0.5, 1:1 DCM/EtOAc). After chromatography separation, each diastereomer was hydrolyzed using sodium methoxide [8] 13 C NMR spectra and NOE experiments, and comparison of the experimental CD spectra with the calculated spectra using TDDFT method [18,19] ( Figure 2). The data of (2R,3S)-23 were in agreement with those reported [1] for the natural product.…”
Section: Resultsmentioning
confidence: 99%
“…The absolute configuration of 1 was established by circular dichroism (CD) spectrum. In a previous paper, 15) it was reported that the S configuration of chiral center (C-13) in five-membered α,β-unsaturated lactone ring exhibits positive Note * To whom correspondence should be addressed. e-mail: jgdai@imm.ac.cn The authors declare no conflict of interest.…”
Section: Resultsmentioning
confidence: 99%